THE UNBORN CHILD AS A PERSON AND ITS LEGAL TREATMENT UNDER BRAZILIAN LAW (CIPEEX, 2025)
This scientific article analyzes the legal status of the unborn child (nascituro) within the Brazilian legal system, addressing its condition as a subject of rights from the moment of conception, albeit without full legal personality. The unborn child, a human being conceived and in intrauterine development, holds a central position in debates concerning human dignity and fundamental rights, particularly in the context of ongoing discussions about possible legislative changes regarding the acceptance of abortion. The research adopts a qualitative approach, based on a literature review and legislative and doctrinal analysis, drawing on authors such as Gonçalves (2023), Diniz (2023), and Tartuce (2025). Three key aspects are examined: the civil capacity of the unborn child, the acquisition of legal personality, and the legal effects attributed to conception. The study highlights the coexistence of different legal theories—natalist, conceptionist, and conditional—which influence normative interpretation in Brazil. Despite the formal adoption of the natalist theory by the Civil Code, which defines the beginning of legal personality as birth with life, there is significant doctrinal and jurisprudential recognition of rights granted to the unborn from conception, such as inheritance rights, prenatal child support (alimentos gravídicos), and the right to life. This represents a significant shift within Brazilian law across its various branches. Infraconstitutional legislation and international treaties, such as the American Convention on Human Rights (Pact of San José, Costa Rica), also guarantee protection for the unborn. The study concludes that Brazilian law, although maintaining formal limitations, is evolving toward providing substantial legal protection to the unborn, in alignment with the constitutional principles of human dignity and the full protection of life. The analysis underscores the importance of legal interpretations that reconcile positive law with scientific advancements and the fundamental values of the Democratic Rule of Law.
Keywords: Unborn child; Legal theories; Legal status